Towards democratic intelligence oversight: Limits, practices, struggles - Ronja Kniep; Lina Ewert; Bernardino Léon Reyes; Félix Tréguer; Emma Mc Cluskey; Claudia Aradau (Review of International Studies, 2024)
Despite its common usage, the meaning of `democratic' in democratic intelligence oversight has rarely been spelled out. In this article, we situate questions regarding intelligence oversight within broader debates about the meanings and practices of democracy. We argue that the literature on intelligence oversight has tended to implicitly or explicitly follow liberal and technocratic ideas of democracy, which have limited the understanding of oversight both in academia and in practice. Thus, oversight is mostly understood as an expert, institutional and partially exclusive arrangement that is supposed to strike a balance between individual freedom and collective security, with the goal of establishing the legitimacy of and trust in intelligence work in a national setting. `Healthy' or `efficient' democratic oversight then becomes a matter of technical expertise, non-partisanship, and the ability to guard secrets. By analysing three moments of struggle around what counts as intelligence oversight across Germany, the UK, and the US, this article elucidates their democratic stakes. Through a practice-based approach, we argue that oversight takes much more agonistic, contentious, transnational, and public forms. However, these democratic practices reconfiguring oversight remain contested or contained by dominant views on what constitutes legitimate and effective intelligence oversight.
Keywords: 320; Advocacy; Democracy; Intelligence Oversight; Litigation; Surveillance; Whistleblowing